Pengembangan Aplikasi Mobile Penyusunan Ransum Pakan Ternak Sapi dan Kambing Menggunakan Framework Ionic - Andriano Eucharistia Wibowo; Herman Tolle; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
An application to compile rations for cattles' meals was developed by a student of Brawijaya University ini 2015. This application is a web-based application that formulate cattles' meal from two kinds of ingredients, that is forage ingredients and concentrate ingredients, to fulfill the daily nutrition or to increase the weight of a cow. The application that is called SunRan (Susun Ransum) used Yii framework in its development. The developer of the application felt that a development for the mobile version in needed. The need encourages the writer to develop the SunRan on a mobile platform. This mobile version of SunRan uses Ionic framework which has a function for developing applications in hybrid system, which is a ixture of system based on website and native. The operating system used to run SunRan Mobile is Android OS. It's done because this operating system is the most opoular operating system, especiallly in Asia, where there are still a lot of people working on a ranch for cows and goats. Besides being used to compile rations for cow's meal, the writer is also adding a new object that hasn't included in the web-based SunRan before, the object is goat. The tests for this mobile application is done twice to prove if the web-based SunRan can be developed into a mobile-based application with an addition of a new object and an utilization of a different framework.